A retrospective real-world study of early short-course remdesivir in non-hospitalized COVID-19 patients at high risk for progression: low rate of hospitalization or death, regardless of immunocompetence status - Ramos-Rincón, José Manuel; Pinargote-Celorio, Héctor; Llenas-García, Jara; Moreno-Pérez, Oscar; González-Cuello, Inmaculada; Gonzalez-de-la-Aleja, Pilar; Martínez-López, Belén; Reus, Sergio; García-López, María; Rodríguez, Juan Carlos; Boix, Vicente; Merino, Esperanza (Frontiers in Pharmacology, 2023)
Introduction: The evidence for remdesivir therapy in immunocompromised patients is scarce. To evaluate remdesivir (RDV) effectiveness and safety in COVID-19 outpatients at high risk for progression in a real-world setting, we compare the outcome in immunocompromised (IC) patients with that in non-immunocompromised patients. Methods: Two hospitals conducted a retrospective study of all adult patients with mild-to-moderate SARS-CoV-2 infection at high risk for disease progression who were treated as outpatients with a 3-day course of RDV (1st January−30th September 2022). The primary effectiveness endpoint was a composite of any cause of hospitalization or death by day 30. A multiple logistic regression model was built to explore the association between immune status and clinical outcome, estimating adjusted odds ratios [aORs (95% CI)]. Results: We have included 211 patients, of which 57% were males, with a median age of 65 years (IQR 53–77), 70.1% were vaccinated (three or four doses), and 61.1% were IC. The median duration of symptoms before RDV treatment was 3 days (IQR 2–5). During follow-up, 14 (6.6%) patients were hospitalized, of which 6 (2.8%) were hospitalized for COVID-19 progression. No patient required mechanical ventilation, and two patients died (non-COVID-19-related). After accounting for potential confounders, only anti-CD20 treatment was associated with the composed outcome [aOR 5.35 (1.02–27.5, 95% CI)], whereas the immunocompetence status was not [aOR 1.94 (0.49–7.81, 95% CI)]. Conclusion: Early COVID-19 outpatient treatment with a 3-day course of remdesivir in vaccinated patients at high risk for disease progression during the Omicron surge had a good safety profile. It was associated with a low rate of all-cause hospitalization or death, regardless of immunocompetence status.